Big Shoes to Fill: An Evaluation Journey in the Footsteps of Daniel L. Stufflebeam - Sherrie-Ann Camilli (The Evaluation Center at Western Michigan University, 2019)
Background: Evaluation has evolved remarkably since the early 1960s, largely due to the innovative contributions of Daniel Stufflebeam and his colleagues. As a pioneer of evaluation methods, some of the notable achievements arising from Stufflebeam's work include the context-input-process-product (CIPP) model, evaluation standards, and evaluation checklists.     Purpose: The purpose of this paper is to explore Daniel Stufflebeam's journey beginning with the early days of evaluation through to his retirement and unfortunate passing at 80 years old in 2017. Key features of the CIPP model are considered within a context of other popular models for comparison with the goal of finding relevance for use of CIPP evaluation in education settings.   Setting: Not applicable.   Intervention: Not applicable.   Research Design: Literature review.   Data Collection and Analysis: Not applicable.   Findings: Stufflebeam's CIPP model and evaluation standards remain prominent in evaluation practices and his legacy will lay the foundation for future evaluators through continued professional development.